High water retention and low shrinkage domestic cement and its preparation method
Patent Information
- Application Number
- CN202611099359.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-23
- Publication Date
- 2026-10-30
AI Technical Summary
[0003]然而,据相关统计,每年因水泥砂浆泛碱、开裂、空鼓、脱落等质量问题进行返修的装修工程数量庞大
1、本发明主要采用铝酸三钙(C3A)含量较高的硅酸盐水泥熟料,C3A的快速水化特性,不仅生成大量微细水化铝酸钙凝胶,凝胶具备大比表面积、强吸附自由水能力,能显著减少泌水、离析,提升砂浆保水性及粘聚性;还可生成产物钙矾石,提高早期强度,缩短工期,为材料的力学性能和长期耐久性提供了关键保障,钙矾石能补偿砂浆因化学减缩、干燥或降温产生的收缩,内部生成预压应力以抵消收缩拉应力,从而有效抑制开裂。
Smart Images

Figure CN123003239A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of building decoration materials technology, specifically to a high water retention and low shrinkage cement for home decoration and its preparation method. Background Technology
[0002] Cement for home decoration is a core basic material in the field of building decoration and renovation. It is widely used in indoor floor leveling, wall plastering, tile bonding, waterproof base treatment of kitchens and bathrooms, and small-scale masonry. Its performance directly determines the ease of construction, appearance quality, and long-term durability of home decoration projects, and is closely related to the safety and comfort of the living environment. With the improvement of residents' living standards, the requirements of the home decoration market for cement have been upgraded from the traditional "strength meeting the standard" to "multi-functional, easy to construct, environmentally friendly and stable". It not only needs to meet the basic mechanical performance requirements, but also puts forward higher standards for key indicators such as water retention, foam stability, and workability.
[0003] However, according to relevant statistics, the number of renovation projects that need to be repaired every year due to quality problems such as efflorescence, cracking, hollowing, and falling off of cement mortar is huge. The existing home decoration cement has the following technical defects in practical application: (1) Insufficient water retention: Home decoration construction is mostly done manually. If the water retention of cement slurry is insufficient, water will easily be lost quickly and water will be separated, resulting in sanding, hollowing, and cracking of walls and floors. Tiles are easy to fall off after being pasted. Existing high water retention solutions generally use bentonite as a water-retaining mineral. However, the layered structure of bentonite is easy to collapse under the strong alkali system of cement. The water retention performance will fail quickly during high temperature construction. Moreover, high bentonite content will greatly increase the water demand, hardening shrinkage is large, and the risk of cracking will be aggravated. (2) Severe shrinkage cracking: During the hardening process of cement-based materials, the shrinkage tensile stress generated by chemical shrinkage, drying and cooling will easily lead to cracking of plaster layer and adhesive layer. Traditional solutions mostly rely on the micro-expansion compensation of ettringite. However, the effect of a single compensation mechanism is limited and it is difficult to meet the crack resistance requirements of thin-layer construction in home decoration. (3) Insufficient bonding strength and efflorescence: The bonding strength between existing cement and substrates such as tiles and blocks is low, which can easily lead to hollowing and falling off; at the same time, free alkali in cement migrates to the surface with water to form efflorescence, which seriously affects the aesthetics of decoration.
[0004] Therefore, developing a type of cement for home decoration that can simultaneously achieve high water retention, low shrinkage, high strength, and efflorescence suppression has become an urgent technical need to be addressed in this field. Summary of the Invention
[0005] The purpose of this invention is to overcome the above-mentioned technical defects and deficiencies, and to provide a high water retention and low shrinkage cement for home decoration and its preparation method. This cement selects green inorganic materials, controls the mineral composition of cement clinker, and uses high water retention admixtures and grinding aids. It employs a composite grinding process and multi-dimensional synergistic regulation of cement performance, so that the cement has high water retention, good workability and low shrinkage characteristics.
[0006] To achieve the above objectives, the technical solution adopted by the present invention is as follows: A type of high water retention and low shrinkage cement for home decoration, comprising the following raw materials by weight percentage: Ordinary Portland cement clinker 62%~67%; 31%~36% of the admixtures; 2%~4% gypsum; And grinding aids comprising 0.05% to 0.2% of the total mass of ordinary silicate cement clinker, admixtures, and gypsum; The mineral composition of ordinary silicate cement clinker by mass percentage includes: 40%~55% C3S, 20%~30% C2S, 8%~12% C3A, and 10%~15% C4AF.
[0007] Furthermore, the blending material consists of the following materials in mass percentage: Fly ash 50%~57%; Limestone 30%~35%; Modified and activated papermaking sludge 7%~9%; 5%~8% ultrafine sepiolite powder.
[0008] Furthermore, the modified and activated papermaking sludge is causticized sludge produced during the alkali recovery process in papermaking. It undergoes the following gradient low-temperature activation pretreatment: the causticized sludge is first pre-dried at 100℃ for 2 hours, then heated to 160~180℃ for constant temperature activation for 1.5 hours, cooled, and sieved to 5~30μm to obtain modified and activated papermaking sludge with a calcium carbonate content of 85%~95%.
[0009] Furthermore, the chemical composition of the ultrafine sepiolite powder, by mass percentage, includes: 54%~60% SiO2 and 21%~25% MgO; the ultrafine sepiolite powder is a fibrous powder with an aspect ratio of 8~12:1 and a specific surface area of 350-400 m². 2 / g.
[0010] Furthermore, the gypsum is a mixed gypsum, composed of natural dihydrate gypsum and anhydrite in a mass ratio of 7:3.
[0011] Furthermore, the grinding aid consists of the following materials by mass percentage: Diethanol monoisopropanolamine 20%~25%; Triisopropanolamine 5%~10%; 1%~3% polyethylene glycol; Hydroxyethyl methylcellulose 0.5%~1%; Glycerin 3%~6%; Anhydrous sodium sulfate 5%~10%; Water content: 55%~60%.
[0012] Furthermore, the diethanol monoisopropanolamine is an 85% aqueous solution of diethanol monoisopropanolamine, the polyethylene glycol is liquid polyethylene glycol 400, and the hydroxyethyl methyl cellulose is hydroxyethyl methyl cellulose with a viscosity of 100,000.
[0013] A method for preparing high water retention and low shrinkage cement for home decoration includes the following steps: S1. Take fly ash, limestone, modified and activated papermaking white mud and ultrafine fibrous sepiolite powder according to the proportion, and premix them at 80 r / min for 15 min to obtain the admixture material for later use. S2. Heat water to 40°C, add glycerin and polyethylene glycol in sequence and stir at 120 r / min to dissolve, then add diethanol monoisopropanolamine and triisopropanolamine, and ultrasonically disperse for 15 min. Finally, add hydroxyethyl methyl cellulose and anhydrous sodium sulfate, and continue ultrasonic dispersion until a completely transparent and homogeneous system is obtained to obtain a grinding aid without agglomeration particles. S3. Ordinary silicate cement clinker, gypsum, and the admixture obtained in S1 are fed into a ball mill and ground in two stages: the first stage is pre-grinding at a speed of 18~21 r / min for 5 min; the second stage is fine grinding at a speed of 23~27 r / min, with the temperature controlled at ≤120℃ throughout the process. During the grinding process, the grinding aid prepared in S2 is uniformly sprayed by high pressure atomization. S4, ground to a 45μm sieve residue of 5%~8%, specific surface area of 350~370m² 2 / kg, after discharge, let stand and age for 20 minutes to obtain the aforementioned home decoration cement.
[0014] Compared with the prior art, the present invention has the following beneficial effects: 1. This invention mainly uses silicate cement clinker with a high content of tricalcium aluminate (C3A). The rapid hydration characteristics of C3A not only generate a large amount of fine hydrated calcium aluminate gel, which has a large specific surface area and strong adsorption capacity for free water, but also significantly reduces bleeding and segregation, and improves the water retention and cohesiveness of mortar. It can also generate ettringite, which improves early strength and shortens the construction period, providing key guarantees for the mechanical properties and long-term durability of the material. ettringite can compensate for the shrinkage of mortar caused by chemical shrinkage, drying or cooling, and generate pre-compression stress inside to offset the shrinkage tensile stress, thereby effectively inhibiting cracking.
[0015] 2. The sepiolite powder used in this invention possesses a unique layered chain crystal structure and well-developed nanoscale micropores. Its structure remains stable and undamaged in the strongly alkaline cement system. Through the reversible adsorption and slow-release effects of the nanopores, it continuously provides internal curing moisture for cement hydration, effectively slowing the rate of moisture loss within the slurry and reducing autogenous shrinkage and drying shrinkage. Its fibrous crystal morphology acts as a microfiber bridging agent in the hardened slurry, inhibiting microcrack propagation and improving the integrity and crack resistance of the cement paste. Simultaneously, sepiolite powder is rich in active SiO2 and MgO, which can undergo a secondary hydration reaction with the cement hydration product Ca(OH)2, generating additional CSH gel and magnesium-rich silicate hydration products. This further densifies the interfacial transition zone, significantly enhancing the interfacial bonding strength between the hardened slurry and the substrate while increasing the density of the cement paste, thus simultaneously achieving high water retention, high strength, and high durability.
[0016] The paper mill lime sludge used in this invention undergoes gradient low-temperature activation pretreatment, where the calcium carbonate and active silica-alumina components synergistically perform multiple functions: On the one hand, the activated lime sludge has optimized particle size distribution, effectively filling the capillaries and microcracks in the cement stone through the micro-aggregate filling effect, improving the density of the hardened paste, blocking water migration channels, thereby improving water retention performance and reducing harmful porosity; on the other hand, the active silica-alumina components in the activated lime sludge can effectively adsorb and solidify the free alkali produced by cement hydration, converting it into a stable insoluble mineral phase, reducing the content of free alkali that can migrate to the surface, thereby effectively inhibiting efflorescence on the wall surface and solving the aesthetic problem of efflorescence in home decoration cement; in addition, the residual appropriate amount of Ca(OH)2 continues to participate in the pozzolanic reaction during the hydration process, synergistically regulating the cement hydration process, optimizing the composition and microstructure of hydration products, ensuring the stable development of early strength, and further reducing drying shrinkage by reducing the content of migratable free alkali, thus giving the cement excellent volume stability and construction adaptability.
[0017] 3. This invention, by strictly controlling grinding process parameters, ensures stable grinding aid performance. This compound grinding aid not only improves grinding efficiency and increases production but also simultaneously enhances the water retention and early strength of cement. Specifically, diethanolamine and triisopropanolamine work synergistically to optimize cement grinding efficiency and particle size distribution, increase the content of fine powder, and improve cement particle bulk density; the lubricating and dispersing effects of glycerol and polyethylene glycol reduce interparticle frictional resistance and decrease mortar water demand; hydroxyethyl methyl cellulose can form an organic-inorganic interpenetrating network structure with ultrafine sepiolite powder, significantly improving the water retention and thixotropic anti-sagging properties of the slurry and extending the open time of home decoration construction; the slow-release buffering effect of polyethylene glycol can suppress the hydration heat release rate, reduce uneven volume expansion caused by hydration temperature rise, and, combined with the internal curing and slow-release water supply effect of sepiolite, jointly reduce chemical shrinkage and drying shrinkage; the polyol amine components synergistically regulate the cement hydration process, promote the early hydration of C3S and C2S, and simultaneously improve the early and later tensile bond strength of the mortar. Attached Figure Description
[0018] Figure 1 This is a SEM image of a 28-day hydration sample of cement for home decoration prepared in Example 1 of the present invention.
[0019] Figure 2 SEM image of the 28-day hydration sample of the cement used in home decoration prepared in Comparative Example 1. Detailed Implementation
[0020] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to embodiments. Obviously, the described embodiments are merely some embodiments of this invention, and not all embodiments. All other embodiments obtained by those skilled in the art based on the embodiments of this invention without creative effort are within the scope of protection of this invention.
[0021] In this embodiment of the invention, the 7-day activity index of fly ash is >72%.
[0022] Example 1, as a preferred embodiment of the present invention, provides the following components and contents of the cement used for home decoration: Ordinary Portland cement clinker 62%; 34% of the materials were admixtures. 4% plaster; And grinding aids comprising 0.2% of the total mass of ordinary silicate cement clinker, admixtures and gypsum.
[0023] The mineral composition of ordinary silicate cement clinker is: C3S 48%, C2S 25%, C3A 10%, and C4AF 12%.
[0024] The admixture consists of the following materials in the following percentages by mass: fly ash 55%; Limestone 30%; 7% modified and activated papermaking white mud; 5% ultrafine sepiolite powder.
[0025] The modified activated papermaking sludge is causticized sludge produced during the alkali recovery process in papermaking. It undergoes the following gradient low-temperature activation pretreatment: the causticized sludge is first pre-dried at 100℃ for 2 hours, then heated to 170℃ and activated at a constant temperature for 1.5 hours. After cooling, it is sieved to 5~30μm to obtain modified activated papermaking sludge with a calcium carbonate content of 90%.
[0026] The chemical composition of ultrafine sepiolite powder, by mass percentage, includes: 57% SiO2 and 23% MgO; ultrafine sepiolite powder is a fibrous powder with an aspect ratio of 10:1 and a specific surface area of 350 m². 2 / g.
[0027] Gypsum is composed of natural dihydrate gypsum and anhydrite in a mass ratio of 7:3.
[0028] The grinding aid consists of the following materials by mass percentage: Diethanol monoisopropanolamine 22%; Triisopropanolamine 7%; Polyethylene glycol 400 2%; Hydroxyethyl methylcellulose (100,000 viscosity) 1%; 4% glycerol; 8% anhydrous sodium sulfate; Water 56%.
[0029] The preparation method of cement for home decoration in this embodiment is as follows: S1. Take fly ash, limestone, modified and activated papermaking white mud and ultrafine fibrous sepiolite powder according to the proportion, and premix them at 80 r / min for 15 min to obtain the admixture material for later use. S2. Heat water to 40°C, add glycerin and polyethylene glycol 400 in sequence and stir at 120 r / min to dissolve, then add diethanol monoisopropanolamine and triisopropanolamine, and ultrasonically disperse for 15 min. Finally, add hydroxyethyl methyl cellulose and anhydrous sodium sulfate, and continue ultrasonically disperse until a completely transparent and homogeneous system is obtained to obtain a grinding aid without agglomerates. S3. Ordinary silicate cement clinker, gypsum, and the admixture obtained in S1 are fed into a ball mill and ground in two stages: the first stage is pre-grinding at 18 r / min for 5 min to break up agglomerated particles; the second stage is fine grinding at 23 r / min, with the temperature controlled at ≤120℃ throughout the process. During the grinding process, the grinding aid prepared in S2 is uniformly sprayed by high pressure atomization. S4, ground to a 45μm sieve residue of 6.5%, specific surface area of 360m². 2 / kg, after discharge, let stand and age for 20 minutes to obtain home decoration cement.
[0030] Example 2, as a preferred embodiment of the present invention, provides the following components and contents of the cement used for home decoration: Ordinary Portland cement clinker 65%; 33% admixtures; 2% plaster; And grinding aids comprising 0.05% of the total mass of ordinary silicate cement clinker, admixtures and gypsum.
[0031] The mineral composition of ordinary silicate cement clinker is: C3S 40%, C2S 30%, C3A 12%, and C4AF 10%.
[0032] The admixture consists of the following materials in the following percentages by mass: fly ash 50%; Limestone 33%; 9% of modified and activated papermaking white mud; 8% ultrafine sepiolite powder.
[0033] The modified activated papermaking sludge is causticized sludge produced during the alkali recovery process in papermaking. It undergoes the following gradient low-temperature activation pretreatment: the causticized sludge is first pre-dried at 100℃ for 2 hours, then heated to 160℃ for constant temperature activation for 1.5 hours, cooled, and sieved to 5~30μm to obtain modified activated papermaking sludge with a calcium carbonate content of 85%.
[0034] The chemical composition of ultrafine sepiolite powder, by mass percentage, includes: 54% SiO2 and 25% MgO; ultrafine sepiolite powder is a fibrous powder with an aspect ratio of 12:1 and a specific surface area of 365 m². 2 / g.
[0035] Gypsum is composed of natural dihydrate gypsum and anhydrite in a mass ratio of 7:3.
[0036] The grinding aid consists of the following materials by mass percentage: Diethanol monoisopropanolamine 20%; Triisopropanolamine 10%; Polyethylene glycol 400 1%; Hydroxyethyl methylcellulose (100,000 viscosity) 0.5%; 3% glycerol; 5% anhydrous sodium sulfate; Water 60.5%.
[0037] The preparation method of cement for home decoration in this embodiment is as follows: S1. Take fly ash, limestone, modified and activated papermaking white mud and ultrafine fibrous sepiolite powder according to the proportion, and premix them at 80 r / min for 15 min to obtain the admixture material for later use. S2. Heat water to 40°C, add glycerin and polyethylene glycol 400 in sequence and stir at 120 r / min to dissolve. Then add diethanol monoisopropanolamine and triisopropanolamine and ultrasonically disperse for 15 min. Finally, add hydroxyethyl methyl cellulose and anhydrous sodium sulfate and continue ultrasonic dispersion until a completely transparent and homogeneous system is obtained to obtain a grinding aid without agglomerates. S3. Ordinary silicate cement clinker, gypsum, and the admixture obtained in S1 are fed into a ball mill and ground in two stages: the first stage is pre-grinding at a speed of 19 r / min for 5 min to break up agglomerated particles; the second stage is fine grinding at a speed of 27 r / min, with the temperature controlled at ≤120℃ throughout the process. During the grinding process, the grinding aid prepared in S2 is uniformly sprayed by high-pressure atomization. S4, ground to a 45μm sieve residue of 6.5%, specific surface area of 370m². 2 / kg, after discharge, let stand and age for 20 minutes to obtain home decoration cement.
[0038] Example 3, as a preferred embodiment of the present invention, provides the following components and contents of the cement used for home decoration: Ordinary Portland cement clinker 67%; 31% of the materials were admixtures. 2% plaster; And grinding aids comprising 0.1% of the total mass of ordinary silicate cement clinker, admixtures and gypsum.
[0039] The mineral composition of ordinary silicate cement clinker is: C3S 55%, C2S 20%, C3A 8%, and C4AF 15%.
[0040] The admixture consists of the following materials in the following percentages by mass: fly ash 58%; Limestone 30%; 7% modified and activated papermaking white mud; 5% ultrafine sepiolite powder.
[0041] The modified activated papermaking sludge is causticized sludge produced during the alkali recovery process in papermaking. It undergoes the following gradient low-temperature activation pretreatment: the causticized sludge is first pre-dried at 100℃ for 2 hours, then heated to 180℃ and activated at a constant temperature for 1.5 hours. After cooling, it is sieved to 5~30μm to obtain modified activated papermaking sludge with a calcium carbonate content of 95%.
[0042] The chemical composition of ultrafine sepiolite powder, by mass percentage, includes: 60% SiO2 and 21% MgO; ultrafine sepiolite powder is a fibrous powder with an aspect ratio of 8:1 and a specific surface area of 360 m². 2 / g.
[0043] Gypsum is composed of natural dihydrate gypsum and anhydrite in a mass ratio of 7:3.
[0044] The grinding aid consists of the following materials by mass percentage: Diethanol monoisopropanolamine 25%; Triisopropanolamine 10%; Polyethylene glycol 400 1%; Hydroxyethyl methylcellulose (100,000 viscosity) 1%; 3% glycerol; 5% anhydrous sodium sulfate; Water 55%.
[0045] The preparation method of cement for home decoration in this embodiment is as follows: S1. Take fly ash, limestone, modified and activated papermaking white mud and ultrafine fibrous sepiolite powder according to the proportion, and premix them at 80 r / min for 15 min to obtain the admixture material for later use. S2. Heat water to 40°C, add glycerin and polyethylene glycol 400 in sequence and stir at 120 r / min to dissolve. Then add diethanol monoisopropanolamine and triisopropanolamine and ultrasonically disperse for 15 min. Finally, add hydroxyethyl methyl cellulose and anhydrous sodium sulfate and continue ultrasonic dispersion until a completely transparent and homogeneous system is obtained to obtain a grinding aid without agglomerates. S3. Ordinary silicate cement clinker, gypsum, and the admixture obtained in S1 are fed into a ball mill and ground in two stages: the first stage is pre-grinding at 18 r / min for 5 min to break up agglomerated particles; the second stage is fine grinding at 25 r / min, with the temperature controlled at ≤120℃ throughout the process. During the grinding process, the grinding aid prepared in S2 is uniformly sprayed by high pressure atomization. S4, ground to a 45μm sieve residue of 6.5%, specific surface area of 365m². 2 / kg, after discharge, let stand and age for 20 minutes to obtain home decoration cement.
[0046] Example 4, as a preferred embodiment of the present invention, provides the following components and contents of the cement used for home decoration: Ordinary Portland cement clinker 66%; 31% of the materials were admixtures. 3% plaster; And grinding aids comprising 0.15% of the total mass of ordinary silicate cement clinker, admixtures and gypsum.
[0047] The mineral composition of ordinary silicate cement clinker is: C3S 45%, C2S 28%, C3A 9%, and C4AF 13%.
[0048] The admixture consists of the following materials in the following percentages by mass: fly ash 57%; Limestone 31%; 7% modified and activated papermaking white mud; 5% ultrafine sepiolite powder.
[0049] The modified activated papermaking sludge is causticized sludge produced during the alkali recovery process in papermaking. It undergoes the following gradient low-temperature activation pretreatment: the causticized sludge is first pre-dried at 100℃ for 2 hours, then heated to 168℃ for constant temperature activation for 1.5 hours, cooled, and sieved to 5~30μm to obtain modified activated papermaking sludge with a calcium carbonate content of 92%.
[0050] The chemical composition of ultrafine sepiolite powder, by mass percentage, includes: 58% SiO2 and 22% MgO; ultrafine sepiolite powder is a fibrous powder with an aspect ratio of 9:1 and a specific surface area of 370 m². 2 / g.
[0051] Gypsum is composed of natural dihydrate gypsum and anhydrite in a mass ratio of 7:3.
[0052] The grinding aid consists of the following materials by mass percentage: Diethanol monoisopropanolamine 23%; Triisopropanolamine 5%; Polyethylene glycol 400 3%; Hydroxyethyl methylcellulose (100,000 viscosity) 0.6%; 3% glycerol; 10% anhydrous sodium sulfate; Water 55.4%.
[0053] The preparation method of cement for home decoration in this embodiment is the same as that in Embodiment 1.
[0054] Example 5, as a preferred embodiment of the present invention, provides the following components and contents of the cement for home decoration: Ordinary Portland cement clinker 62%; 36% admixtures; 2% plaster; And grinding aids comprising 0.05% of the total mass of ordinary silicate cement clinker, admixtures and gypsum.
[0055] The mineral composition of ordinary silicate cement clinker is: C3S 50%, C2S 22%, C3A 12%, and C4AF 15%.
[0056] The admixture consists of the following materials in the following percentages by mass: fly ash 50%; Limestone 35%; 8% modified and activated papermaking white mud; 7% ultrafine sepiolite powder.
[0057] The modified activated papermaking sludge is causticized sludge produced during the alkali recovery process in papermaking. It undergoes the following gradient low-temperature activation pretreatment: the causticized sludge is first pre-dried at 100℃ for 2 hours, then heated to 175℃ and activated at a constant temperature for 1.5 hours. After cooling, it is sieved to 5~30μm to obtain modified activated papermaking sludge with a calcium carbonate content of 88%.
[0058] The chemical composition of ultrafine sepiolite powder, by mass percentage, includes: 55% SiO2 and 23% MgO; ultrafine sepiolite powder is a fibrous powder with an aspect ratio of 11:1 and a specific surface area of 360 m². 2 / g.
[0059] Gypsum is composed of natural dihydrate gypsum and anhydrite in a mass ratio of 7:3.
[0060] The grinding aid consists of the following materials by mass percentage: Diethanol monoisopropanolamine 21%; Triisopropanolamine 6%; Polyethylene glycol 400 2%; Hydroxyethyl methyl cellulose (100,000 viscosity) 0.9%; Glycerin 6%; Anhydrous sodium sulfate 6%; Water 58.1%.
[0061] The preparation method of cement for home decoration in this embodiment is the same as that in Embodiment 1.
[0062] Comparative Example 1 differs from Example 1 in that no modified activated papermaking white mud is added to the blended material, while the remaining components and preparation methods are the same as in Example 1.
[0063] Comparative Example 2 differs from Example 1 in that: no ultrafine sepiolite powder is added to the blended material, while the other components and preparation methods are the same as in Example 1.
[0064] Comparative Example 3 differs from Example 1 in that it does not use modified activated papermaking sludge, but instead uses causticized sludge (non-modified activated sludge) generated during the papermaking alkali recovery process. It is used directly after drying and pulverizing. The remaining components and preparation methods are the same as in Example 1.
[0065] Comparative Example 4 differs from Example 1 in that the ultrafine sepiolite powder in the admixture is replaced with sodium-based bentonite in equal amounts, while the remaining components and preparation methods are the same as in Example 1.
[0066] Comparative Example 5 differs from Example 1 in that hydroxyethyl methyl cellulose is not added to the grinding aid, while the remaining components and preparation methods are the same as in Example 1.
[0067] Performance testing was conducted on the cements prepared in Examples 1-5 and Comparative Examples 1-5. Cement strength was tested according to GB / T 17671-2021 "Test Method for Strength of Cement Mortar"; standard consistency water requirement and setting time were tested according to GB / T 1346-2011 "Test Method for Standard Consistency Water Requirement, Setting Time and Soundness of Cement"; drying shrinkage was tested according to JC / T 603-2004 "Test Method for Drying Shrinkage of Cement Mortar"; and tensile bond strength was tested according to JC / T 547-201 "Tile Adhesive". The test results are shown in Table 1.
[0068] Table 1 Test Results
[0069] As shown in Table 1, different admixtures have a significant impact on the material properties. Compared with comparative examples 1 to 5, the cement of this invention has higher compressive strength, water retention rate, and bonding strength, as well as lower shrinkage rate, which can effectively improve the problems of easy hollowing and cracking of cement. In addition, although the cement has high water retention, the standard consistency water consumption is increased, but the setting time of the cement is extended, which is beneficial to extend the open time during the construction of cement for home decoration.
[0070] The following analysis of the microstructure of the 28-day hydrated samples from Example 1 and Comparative Example 1 was performed using scanning electron microscopy (SEM).
[0071] Figure 1 This is a SEM image of a 28-day hydration sample of cement used in home decoration prepared in Example 1 of this invention. Figure 2 SEM image of the 28-day hydration sample of the cement used in home decoration prepared in Comparative Example 1.
[0072] from Figure 1 As can be seen, the hydration product of Example 1 is mainly composed of flocculent CSH gel clusters. A large number of flocculent gels cross-link and overlap, forming a continuous and dense network structure with few pores and microcracks, resulting in high overall structural density. This indicates that the present invention, through the synergistic effect of activating paper mill lime sludge and ultrafine sepiolite powder, promotes the secondary hydration reaction of cement, generating a large amount of additional CSH gel to fill capillary pores and interfacial transition zones, thereby significantly improving the density and interfacial bonding strength of the hardened paste.
[0073] from Figure 2 It can be seen that the hydration products of Comparative Example 1 are mainly plate-like structures, with a significant reduction in flocculent gel content, a relatively loose structure, numerous pores and microcracks, insufficient interparticle overlap, and poor overall structural density. This indicates that without the addition of paper mill lime sludge, the pozzolanic activity of the admixture is insufficient, the degree of secondary hydration reaction is low, and the amount of hydration products generated is small, which cannot fully fill the internal pores of the slurry, resulting in a loose structure in the hardened slurry.
[0074] The above microstructure analysis shows that the present invention significantly improves the microstructure of cement hydration products by synergistically combining activated paper mill lime sludge with ultrafine sepiolite powder. This is consistent with the high water retention, high bonding strength and low shrinkage exhibited in Example 1 in terms of macroscopic performance, further verifying the effectiveness of the technical solution of the present invention.
[0075] Finally, it should be noted that the above embodiments are merely preferred embodiments of the present invention used to illustrate the technical solutions of the present invention, and are not intended to limit the invention, nor are they intended to limit the patent scope of the present invention. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some or all of the technical features therein. These modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention. That is to say, any changes or refinements made to the main design concept and spirit of the present invention that are not of substantial significance, but whose technical problems are still consistent with the present invention, should be included within the protection scope of the present invention. In addition, the direct or indirect application of the technical solutions of the present invention to other related technical fields are similarly included within the patent protection scope of the present invention.
Claims
1. A type of high water retention and low shrinkage cement for home decoration, characterized in that, Raw materials include the following percentage by weight: Ordinary Portland cement clinker 62%~67%; 31%~36% of the admixtures; 2%~4% gypsum; And grinding aids comprising 0.05% to 0.2% of the total mass of ordinary silicate cement clinker, admixtures, and gypsum; The mineral composition of ordinary silicate cement clinker by mass percentage includes: 40%~55% C3S, 20%~30% C2S, 8%~12% C3A, and 10%~15% C4AF.
2. The cement for home decoration according to claim 1, characterized in that, The blended material is composed of the following materials by mass percentage: Fly ash 50%~58%; Limestone 30%~35%; Modified and activated papermaking sludge 7%~9%; 5%~8% ultrafine sepiolite powder.
3. The cement for home decoration according to claim 2, characterized in that, The modified activated papermaking sludge is causticized sludge produced during the alkali recovery process in papermaking. It undergoes the following gradient low-temperature activation pretreatment: the causticized sludge is first pre-dried at 100℃ for 2 hours, then heated to 160~180℃ for constant temperature activation for 1.5 hours, cooled, and sieved to 5~30μm to obtain modified activated papermaking sludge with a calcium carbonate content of 85%~95%.
4. The cement for home decoration according to claim 2, characterized in that, The chemical composition of ultrafine sepiolite powder, by mass percentage, includes: 54%~60% SiO2 and 21%~25% MgO; ultrafine sepiolite powder is a fibrous powder with an aspect ratio of 8~12:1 and a specific surface area of 350-400 m². 2 / g.
5. The cement for home decoration according to claim 1, characterized in that, The gypsum is a mixed gypsum, composed of natural dihydrate gypsum and anhydrite in a mass ratio of 7:
3.
6. The cement for home decoration according to claim 1, characterized in that, The grinding aid consists of the following materials by mass percentage: Diethanol monoisopropanolamine 20%~25%; Triisopropanolamine 5%~10%; 1%~3% polyethylene glycol; Hydroxyethyl methylcellulose 0.5%~1%; Glycerin 3%~6%; Anhydrous sodium sulfate 5%~10%; Water content: 55%~60%.
7. The cement for home decoration according to claim 6, characterized in that, Diethanol monoisopropanolamine is an 85% aqueous solution of diethanol monoisopropanolamine, polyethylene glycol is liquid polyethylene glycol 400, and hydroxyethyl methyl cellulose is hydroxyethyl methyl cellulose with a viscosity of 100,000.
8. The method for preparing home decoration cement according to any one of claims 1 to 7, characterized in that, Includes the following steps: S1. Take fly ash, limestone, modified and activated papermaking white mud and ultrafine fibrous sepiolite powder according to the proportion, and premix them at 80 r / min for 15 min to obtain the admixture material for later use. S2. Heat water to 40°C, add glycerin and polyethylene glycol in sequence and stir at 120 r / min to dissolve, then add diethanol monoisopropanolamine and triisopropanolamine, and ultrasonically disperse for 15 min. Finally, add hydroxyethyl methyl cellulose and anhydrous sodium sulfate, and continue ultrasonic dispersion until a completely transparent and homogeneous system is obtained to obtain a grinding aid without agglomeration particles. S3. Ordinary silicate cement clinker, gypsum, and the admixture obtained in S1 are fed into a ball mill and ground in two stages: the first stage is pre-grinding at a speed of 18~21 r / min for 5 min; the second stage is fine grinding at a speed of 23~27 r / min, with the temperature controlled at ≤120℃ throughout the process. During the grinding process, the grinding aid prepared in S2 is uniformly sprayed by high pressure atomization. S4, ground to a 45μm sieve residue of 5%~8%, specific surface area of 350~370m² 2 / kg, after discharge, let stand and age for 20 minutes to obtain the aforementioned home decoration cement.